5-Acetamido-1H-pyrazole-4-carboxamide monohydrate - Lhoussaine El Ghayati; Youssef Ramli; El Mokhtar Essassi; Mohamed Labd Taha; Joel T. Mague (IUCrData, 2016)
There are two independent molecules of the title carboxamide compound, C6H8N4O2·H2O, as well as two independent water molecules in the asymmetric unit. The two independent carboxamide molecules differ primarily in the relative orientations of the peripheral methyl and amino groups. Intramolecular N—H...O hydrogen bonds assist in determining the orientations of the acetamido substituents. The three-dimensional crystal packing is directed by a large network of O—H...O, N—H...O, C—H...O and C—H...N hydrogen bonds.